2022
DOI: 10.1523/eneuro.0225-22.2022
|View full text |Cite
|
Sign up to set email alerts
|

Theta-Phase Connectivity between Medial Prefrontal and Posterior Areas Underlies Novel Instructions Implementation

Abstract: Implementing novel instructions is a complex and uniquely human cognitive ability, that requires the rapid and flexible conversion of symbolic content into a format that enables the execution of the instructed behavior. Preparing to implement novel instructions, as opposed to their mere maintenance, involves the activation of the instructed motor plans, and the binding of the action information to the specific context in which this should be executed. Recent evidence and prominent computational models suggest … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
7
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 9 publications
(11 citation statements)
references
References 101 publications
4
7
0
Order By: Relevance
“…Then, these values were correlated with the classification AUC per participant and competition condition averaged within the 1150 ms to 1550 ms time window. Finally, we performed a mediation analysis to investigate if the anticipatory theta power acted as a mediator between the competition manipulation and the speed of responses (e.g., Formica et al, 2022). To do so, we used trial-by-trial RT and theta power data, averaging the power values within 100-900 ms after cue presentation (same time window as above).…”
Section: Time-frequency Analysismentioning
confidence: 99%
See 2 more Smart Citations
“…Then, these values were correlated with the classification AUC per participant and competition condition averaged within the 1150 ms to 1550 ms time window. Finally, we performed a mediation analysis to investigate if the anticipatory theta power acted as a mediator between the competition manipulation and the speed of responses (e.g., Formica et al, 2022). To do so, we used trial-by-trial RT and theta power data, averaging the power values within 100-900 ms after cue presentation (same time window as above).…”
Section: Time-frequency Analysismentioning
confidence: 99%
“…On one hand, previous studies have shown a behavioral improvement when preparatory activity patterns associated with the target are more segregable (González-García et al, 2017; Peelen & Kastner, 2011; Soon et al, 2013; Stokes et al, 2009), when the dimensions to attend are better distinguished (Hall-McMaster et al, 2019) or when the working-memory load of the task is better represented (Manelis & Reder, 2015). On the other hand, preparatory theta power in frontocentral electrodes has been related to a more consistent behavior on task-switching paradigms (Cooper et al, 2017) or to a necessary step to accurate fast responses (Formica et al, 2022). However, the relationship between anticipated coding of specific information across contexts, theta power and behavioral performance remains uncertain.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…All ERP analyses were based on mean amplitude, as recommended by Luck and colleagues 127 . We analysed ERPs at a whole brain level using a time-point clusterbased permutation analysis with 1000 repetitions (using p < 0.05 to identify significant cluster differences), Monte-Carlo correction in the 0-1000 ms time window on all electrodes, and cluster comparisons within and between groups to assess neural pattern reliability and robustness over neighbouring data points 128,129 . In addition, analyses using all electrodes were used to capture potential data-driven modulations at the all-electrode level, which can be relevant in ageing and clinical populations where shifts in neural activation might be observed 130 .…”
Section: Eeg Analysesmentioning
confidence: 99%
“…Despite the general dichotomy, abstract task representations are not constrained to frontal cortex, but are also observed in posterior sensory cortex [14][15][16]. These distributed task representations are enhanced during goal implementation compared to pure goal maintenance, which are accompanied by increased long-range functional connectivity [17] and may reflect a spreading of task information from frontal cortex during the active execution of control processes. Nevertheless, how the distributed task representations emerge and communicate with specific sensory information is still unclear.…”
Section: Introductionmentioning
confidence: 99%